Features of Indicators of Press Cake Obtained from Cotton Seeds - Akhmedov Azimjon Normuminovich, Abdurakhimov Saidakbar Abdurakhmonovich (International Journal of Advanced Science and Technology, 2020)
This article discusses the Studies of the characteristics of indicators of press cake obtained from a mixture of III-IV varieties confirm the need to take into account their values ​​when improving the technology for producing press oil from low-grade cotton seeds.